The Influence of Price and Product Quality on Sunan Doe Students' Purchasing Decisions on Shopee - Wahyudi, Zaenul; Amrullah, Amdi (Jurnal Riset Ilmu Pendidikan, 2025)
This study aims to analyze the influence of price and product quality on purchasing decisions of students at the Sunan Doe Islamic Studies Institute on the Shopee platform. The research method used is descriptive quantitative with multiple linear regression analysis techniques, t-test, F-test, and coefficient of determination. The research sample of 82 respondents was selected using the Slovin formula from a population of 431 students. The results show that partially, price has a positive and significant effect on purchasing decisions by 12.1%, while product quality has a positive and significant effect by 53.3%. Simultaneously, price and product quality have a significant effect on purchasing decisions by contributing 57.6%, while the remaining 42.4% is influenced by other variables outside this study. These findings indicate that improving product quality and offering competitive prices can encourage purchasing decisions in e-commerce, especially among students. Research recommendations emphasize the importance of quality- and price-based marketing strategies that are in line with consumer perceptions.